Hi,
The function `join` flattens a double-layered monad into one layer and its type signature is
join :: (Monad m) => m (m a) -> m a
But when the first argument supplied is `(,)`, the type signature becomes
join (,) :: b -> (b, b)
in ghci. The monad constraint is lost when supplied the first argument. So my question is why the type constraint is lost and what monad is supplied here.
Regards, Qingbo Liu
_______________________________________________ Beginners mailing list [hidden email] http://mail.haskell.org/cgi-bin/mailman/listinfo/beginners |
If you type :i Monad in ghci, you will see this instance What this means is a function where the first argument is of type 'r'... is a monad. You can in fact use do notation / return on a tuple to manipulate its second argument monadically.instance Monad ((->) r) So let's look at what that does to the type signature of join when 'm' is ((->) b) join :: Monad m => m (m a) -> m a -- m = ((->) b) join :: ((->) b ((->) b a)) -> (((->) b a)) Now we just have to move the arrows from prefix to infix. Let's do it step by step. join :: ((->) b (b -> a)) -> (b -> a) join :: (b -> (b -> a)) -> (b -> a) x -> (y -> z) is equivalent to x -> y -> z join :: (b -> b -> a) -> (b -> a) join :: (b -> b -> a) -> b -> a So now when you put an operator into it that takes two arguments (,) :: a -> b -> (a,b) You get the type you saw. join (,) :: b -> (b, b) On Fri, Dec 8, 2017 at 10:37 AM, Quentin Liu <[hidden email]> wrote:
_______________________________________________ Beginners mailing list [hidden email] http://mail.haskell.org/cgi-bin/mailman/listinfo/beginners |
Thanks for the explanation. But why did Haskell pick up the Reader monad in particular? Is this part of the HM type inference rule?
Regards, Qingbo Liu
On Dec 8, 2017, 13:12 -0500, David McBride <[hidden email]>, wrote:
_______________________________________________ Beginners mailing list [hidden email] http://mail.haskell.org/cgi-bin/mailman/listinfo/beginners |
Free forum by Nabble | Edit this page |